Translation Strategies of Cultural Terms in Gadis Kretek Series - Ni Km. Dirtania Surti Larasati; Made Susini; I Nyoman Kardana (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2026)
Abstract: This study examines the translation of cultural terms in the Indonesian series Gadis Kretek, which portrays various cultural elements related to social life, traditions, and the kretek industry. Translating cultural terms in audiovisual media presents significant challenges due to cultural differences and the lack of direct equivalence between the source and target languages. Therefore, this study aims to identify the types of cultural terms and analyze the translation strategies used in the English subtitles of the series. This research employs a qualitative descriptive method. The data were collected from dialogues and their corresponding English subtitles. The analysis is based on Newmark’s (1988) cultural categories and Baker’s (2011) translation strategies. The findings reveal that several categories of cultural terms are present, including material culture, social organization, customs, activities, and cultural concepts. The results also show that various translation strategies are applied, such as translation by using a more general word, neutral/less expressive word, cultural substitution, loan word, paraphrase (related and unrelated), omission, and illustration. Notably, among the 152 cultural words found, paraphrasing using related words is the dominant strategy applied (34.21 %). Furthermore, the selection of translation strategies is contextually driven, depending on the characteristics of the cultural terms and the communicative needs of the target audience. This balanced use of strategies demonstrates the translator’s effort to preserve cultural meaning while ensuring clarity and accessibility for international viewers.